1983
DOI: 10.1128/iai.39.1.476-479.1983
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine Lymphocyte Mitogen Responses by Exopolysaccharide from Capnocytophaga ochracea

Abstract: An extracellular polysaccharide was purified from culture supernatants of Capnocytophaga ochracea 25, a gram-negative bacillus associated with human periodontal disease. The extracellular polysaccharide suppressed in vitro mitogenic responses of murine splenic lymphocytes to concanavalin A and lipopolysaccharide. This suppression wad dose dependent, persisted up to 120 h, and was not caused by direct toxicity of the extracellular polysaccharide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…com/onlineopen#OnlineOpen_Terms production of oral bacteria is associated with persistent infections in the oral cavity (Yamane et al 2009. Capnocytophaga ochracea found in periodontal disease has been shown to produce mannose-rich EPS that can suppress murine lymphocyte mitogen responses and activate human complement response (Bolton & Dyer 1983, 1986, Dyer & Bolton 1985. It was reported that some clinical isolates of Prevotella intermedia and P. nigrescens isolated from chronic periodontitis lesions produce EPSs in a sucrose-independent manner and form biofilms that contribute to their virulence (Fukushima et al 1992, Yamane et al 2005, Yamanaka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…com/onlineopen#OnlineOpen_Terms production of oral bacteria is associated with persistent infections in the oral cavity (Yamane et al 2009. Capnocytophaga ochracea found in periodontal disease has been shown to produce mannose-rich EPS that can suppress murine lymphocyte mitogen responses and activate human complement response (Bolton & Dyer 1983, 1986, Dyer & Bolton 1985. It was reported that some clinical isolates of Prevotella intermedia and P. nigrescens isolated from chronic periodontitis lesions produce EPSs in a sucrose-independent manner and form biofilms that contribute to their virulence (Fukushima et al 1992, Yamane et al 2005, Yamanaka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these microorganisms have several features which would warrant their being considered periodontal pathogens. They have been shown to produce an immunosuppressive exopolysaccharide (5,6), to adversely affect neutrophil function (58), and to produce a bone-resorbing lipopolysaccharide (31), and they have been implicated to have tissue-invasive capabilities (11). In addition, they have been shown to hydrolyze immunoglobulins A and G (33) and to produce a superoxide dismutase (25).…”
mentioning
confidence: 99%
“…Among the components of subgingival plaque, anaerobic gram-negative rods including Captwcytophaga spp., Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans have been implicated as etiological agents in periodontal disease (10,19). Possible virulence factors of Capnocytophaga such as an inhibitor of chemotaxis of polymorphonuclear leukocytes (18), a lymphocyte alteration factor (1), an immunoglobulin protease (3,13), phospholipase A2 (17) and superoxide dismutase (8) have been characterized. However, growth of this microorganism in the periodontal area is necessary for these pathogenic factors to affect the periodontium.…”
mentioning
confidence: 99%